Elicitation of natural products biosynthesis from endophytic microorganisms´ interactions - Caraballo Rodríguez, Andrés Mauricio (2017)
In order to continue with the study of natural products from previously isolated endophytes of the Brazilian medicinal plant Lychnophora ericoides, the main goal of this work focused on the metabolic exchange of endophytic microorganisms from this plant. As it has been demonstrated during the last years, elicitation of different molecules is consequence of microbial interactions, mainly due to the need to compete, survive and establish microbial communities in shared environments. Recent mass spectrometry related approaches, such as imaging and molecular networking, in combination with purification and structural elucidation were applied to the current study of the microbial interactions of endophytes. During this study, several chemical families were identified, such as polyene macrocycles, pyrroloindole alkaloids, leupeptins, angucyclines, siderophores, amongst others. Amongst the polyene macrocycles, the well-known antifungal amphotericin B was identified as a biosynthetic product of the endophytic actinobacteria Streptomyces albospinus RLe7. When S. albospinus RLe7 interacted with an endophytic fungus, Coniochaeta sp. FLe4, a red pigmentation was observed. A new fungal compound was detected from microbial interactions. Isolation and structure elucidation of this new compound enabled to demonstrate the elicitation of fungal secondary metabolites by amphotericin B, an actinobacterial metabolite. It was also demonstrated the elicitation of griseofulvin and its analogue dechlorogriseofulvin from another endophytic fungus, FLe9, as a consequence of exposition to amphotericin B. In addition, investigation of the chemical profile of another endophytic actinobacteria, S. mobaraensis RLe3, led to reveal this strain as angucycline-derivatives producer. Besides that, coculturing of this actinobacteria against Coniochaeta sp. FLe4 also demonstrated elicitation of angucycline analogues. In conclusion, this study demonstrated elicitation of natural products from microbial interactions as well as new compounds from endophytes from L. ericoides and contributed to the identification of microbial metabolites